Islamic Law and the Concept of Prophetic-Based Economic Welfare - Syafruddin Syafruddin; Mukhlishin Mukhlishin (Budapest International Research and Critics University, 2022)
Economic welfare is a topic that is often studied in the social sphere, especially in developing countries including Indonesia. Even in Law Number 11 of 2009, the government has specifically regulated social welfare, so that what is the state's goal, namely social welfare for all Indonesian people, can be realized into reality. In the concept of economic welfare, Islam views equity and justice as one of the keys to social welfare. This welfare is the maqashid (goal) of syara' or Islamic law in the economic field. In this regard, the Islamic economic system has attempted to eliminate the cumulative aspect with the philanthropic movement as the antithesis of the modern capitalist system which is individualistic. This study will describe islami law and the concept of prophetic-based economic welfare. This study uses a literature review method. The results show that the concept of prophetic-based economic welfare is the liberation of humans from economic exploitation, inequality, poverty, and at the same time increasing the quality of service to God. The welfare of the people as one of the pillars in the development of Islamic law is related to maqashid (the intent and purpose of syara' law). Maqashid itself as the basis in the formulation of Islamic law through a discipline of knowledge about the rules contained in the books of thought of the scholars (fiqh).